2016
DOI: 10.1159/000447934
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Renal Syndrome Type 4: The Correlation Between Cardiorenal Ultrasound Parameters

Abstract: Bakground/Aims: Cardiovascular diseases represent the leading causes of morbidity and mortality in patients with cronich kidney disease (CKD). The pathogenesis includes a complex, bidirectional interaction between heart and kidney termed cardiorenal syndrome type 4. The aim of study was to evaluate the association between renal and cardiovascular ultrasonographic parameters and identify early markers of cardiovascular risk. Methods: A total of 35 patients with CKD and 25 healthy controls, were enrolled and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
1
10
1
5
Order By: Relevance
“…28 In CKD patients, the development and progression of ventricle dysfunction occurred with inflammation and mineral metabolism disorders. 29 Inflammation and oxidative stress have been linked to the pathogenesis of plaque formation and plaque rupture, 30 both of which are associated with worse cardiovascular outcomes. 31 The present study found no differences in traditional risk factors between patients with and without cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…28 In CKD patients, the development and progression of ventricle dysfunction occurred with inflammation and mineral metabolism disorders. 29 Inflammation and oxidative stress have been linked to the pathogenesis of plaque formation and plaque rupture, 30 both of which are associated with worse cardiovascular outcomes. 31 The present study found no differences in traditional risk factors between patients with and without cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Активно изуча-ется также влияние минерального обмена и на ПЖ при почечной дисфункции [33][34][35]. В частности, признаки гиперпаратиреоза, гиперфосфатемии, де-фицита витамина Д и кальцификации сосудов в ас-социации с КРС тип 4 определялись уже на ранних стадиях ХБП [13,34]. Патогенетически гиперурикемия может выступать в качестве инициирующего агента для окислительно-го стресса, воспаления, эндотелиальной дисфункции и развития системного атеросклероза, но его роль все еще остается не до конца выясненной.…”
Section: Introductionunclassified
“…Известно, что ЛЖ берет свое начало от первичной оболочки сердца, тогда как ПЖ возникает из передней части сердца, ЛЖ имеет форму эллипса, тогда как ПЖ тре-угольника. Кроме того, миокард ЛЖ толще и имеет большую массу, чем ПЖ и, следовательно, лучше приспособлен к перегрузке давлением, в то время как более податливый ПЖ лучше переносит пере-грузку объемом [11][12][13]. Показатель систолической экскурсии плоскости три-куспидального кольца (TAPSE), наряду с легочным артериальным давлением (ЛАД), один из широко из-ученных методов допплеровской Эхо-КГ оценки ПЖ и ассоциирован с неблагоприятными исходами [47].…”
Section: Introductionunclassified
See 2 more Smart Citations